2020
DOI: 10.3390/cancers12102806
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches to Target Mutant FLT3 Leukaemia

Abstract: Fms-like tyrosine kinase 3 (FLT3) is a member of the class III receptor tyrosine kinases (RTK) and is involved in cell survival, proliferation, and differentiation of haematopoietic progenitors of lymphoid and myeloid lineages. Oncogenic mutations in the FLT3 gene resulting in constitutively active FLT3 variants are frequently found in acute myeloid leukaemia (AML) patients and correlate with patient’s poor survival. Targeting FLT3 mutant leukaemic stem cells (LSC) is a key to efficient treatment of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 142 publications
(177 reference statements)
0
18
0
Order By: Relevance
“…Analogously, cSCC, which arises from KCs upon lineage commitment for the fully cornified epidermis [ 166 ], is a more amenable target for PD-1 blockade than mucosal SCC or BCC [ 186 , 187 , 188 , 189 ]. By extension, the differentiation treatment of acute promyelocytic leukemia with tretinoin (all- trans -retinoic acid) [ 237 ] or acute myeloid leukemia with inhibitors of FMS-like tyrosine kinase 3 [ 238 ] reprograms gene expression. However, this sometimes provokes the differentiation syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, cSCC, which arises from KCs upon lineage commitment for the fully cornified epidermis [ 166 ], is a more amenable target for PD-1 blockade than mucosal SCC or BCC [ 186 , 187 , 188 , 189 ]. By extension, the differentiation treatment of acute promyelocytic leukemia with tretinoin (all- trans -retinoic acid) [ 237 ] or acute myeloid leukemia with inhibitors of FMS-like tyrosine kinase 3 [ 238 ] reprograms gene expression. However, this sometimes provokes the differentiation syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…ITD-FLT3 mutations in human AML stem cells are present in 20–30% of AML patients and have been implicated in the poor prognosis and refractory phenotype of this disease [ 77 , 78 , 79 , 80 , 81 , 82 ]. Onish et al reported that ITD-FLT3 mutations enhance the leukemic cell migration toward the chemokine Cxcl12 by inhibiting the downregulation of ROCK1 and dephosphorylation of MYPT1 [ 76 , 83 ]. This can result in the hematopoietic stem cells being retained in the bone marrow and protected from AML therapy [ 76 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The documentation of recurring driver mutations in genes encoding tyrosine kinase leading to the development of molecular targeted treatment strategies designed to increase the outcome of acute myeloid leukemia patients. 63 The FLT3 is the most frequently mutated gene in AML, with internal tandem duplications within a juxta-membrane domain (FLT3-ITD) or missense mutation in the tyrosine kinase domain which accounts for 30%-35% of AML patients at diagnosis. 64 It has appeared as a potential therapeutic target and therefore encourages the synthesis of FLT3 tyrosine kinase inhibitors.…”
Section: Fms-like Tyrosine Kinase 3 As a Therapeutic Target In Leukemiamentioning
confidence: 99%